Pengaruh Media Audio Visual Berbasis Aplikasi YouTube terhadap Akurasi Tembakan pada Ekstrakurikuler Panahan SMA Al Hikmah Surabaya - Aldha Citra Octavia; Faridha Nurhayati (Journal on Education, 2024)
Archery is a sport that uses a bow to shoot arrows at a target. To prevent boredom in learning, YouTube-based audiovisual media was implemented to improve shooting accuracy. This study aims to measure the impact of this media on the shooting accuracy of archery extracurricular participants at SMA Al Hikmah Surabaya. The method used was quantitative with a Quasi-Experimental design, specifically the Randomized Control Group Pretest-Posttest Design. The study population consisted of 38 students divided into experimental and control groups. The research was conducted over one month with six sessions. Data analysis using paired t-tests showed a significant difference between the pretest and posttest in the experimental group (0.010 < 0.05), but no difference in the control group (0.878 > 0.05). Independent samples tests indicated no significant difference between pretest and posttest in both groups (0.119 > 0.05). The experimental group showed an accuracy improvement of 6.59%, while the control group showed only a 0.7% improvement. In conclusion, the use of YouTube-based audiovisual media is effective in improving the shooting accuracy of archery extracurricular participants at SMA Al Hikmah Surabaya.